DYNAMIC ESTABLISHMENT OF PONDOK PESANTREN IN THE MINORITY AREA OF JAYAPURA CITY - Zulihi, Zulihi; Garancang, Sabaruddin; Abunawas, Kamaluddin; Damopolii, Muljono (Program Pascasarjana, UIN Alauddin Makassar, 2019)
This paper discusses the dynamics of the establishment of Islamic boarding schools in the minority areas of Jayapura City. This research method is a qualitative research with the approach used is the phenomenological approach and scientific approaches in the form of sociological and historical. The source of the data of this research is the boarding school caretakers, religious teachers, students, community leaders, traditional leaders, coaches, mentors, educators, and the community. Furthermore, the data collection methods used are observation, interview, documentation, and triangulation. The next stage is data processing techniques and data analysis is done through data reduction, data presentation, and data verification. The results of this study indicate that there are three concepts that become the dynamics of the establishment of huts in minority areas, namely: 1) History of its establishment including: there are indications of apostasy in remote areas of transimigration in Jayapura and Keerom Papua, the assumption of the Islamization of the majority of people in Jayapura, the existence of mosques which is very quiet from the pilgrims, the assumption of Islamic boarding schools as a stronghold of Muslims, and the assumption that Islamic boarding schools print human resources with a radical mindset, the involvement of traditional leaders. 2) Institutional development, including: formal and non-formal education. 3) Contributions of Islamic boarding schools include: the social religious field, the field of religious harmony, and the cultural field based on local wisdom.